The Godfather, part III - Coppola, Francis Ford (Quezon City : Magnavision, 1990)
One of the greatest sagas in movie history continues. In the third film in the epic Corleone trilogy, Al Pacino reprises the role of powerful family leader Michael Corleone. Now in his 60s , Michael is dominated by two passions: freeing his family from crime and finding a suitable successor. That successor could be fiery Vincent (Andy Garcia)... but he may also be the spark that turns Michael's hope of business legitimacy into an inferno of mob violence. Francis Ford Coppola directs Pacino, Garcia, Diane Keaton, Talia Shire, Eli Wallach, Sofia Coppola, Joe Mantegna and others in this exciting, long-awaited film that masterfully explores the themes of power, tradition, revenge and love. Seven Academy Award nominations for 1990 were the result, including Best Picture.